La iglesia y el estado en Veracruz, 1840-1940 - Williman, John B., Malo Zozaya, Miguel J. ((SepSetentas ;, 1976)
El libro es una historia de las relaciones entre el Estado de Veracruz y la iglesia de 1840 a 1940.